Usual adult occupation and risk of prostate cancer in West African men: the Ghana Prostate Study. Issue 2 (7th December 2018) - Adler, Colin; Friesen, Melissa C; Yeboah, Edward D; Tettey, Yao; Biritwum, Richard B; Adjei, Andrew A; Tay, Evelyn; Okyne, Victoria; Mensah, James E; Truelove, Ann; Yang, Baiyu; Kelly, Scott P; et al.
Abstract : Objectives: Established prostate cancer (PCa) risk factors include age, family history of PCa and African ancestry. Studies, mostly among highly screened, predominantly European ancestral populations, suggest that employment in certain occupations (eg, farming, military) may also have an increased risk for PCa. Here, we evaluated the association between usual adult occupation and PCa risk in Ghanaian men, a population with historically low rates of PCa screening. Methods: The Ghana Prostate Study is a case-control study of PCa that was conducted from 2004 to 2012 in 749 cases and 964 controls. In-person interviews were conducted to collect information from participants, including longest held job. Industrial hygienists classified job titles into occupational categories. Unconditional logistic regression was used to calculate ORs and 95% CIs for the association between longest held job and PCa risk (overall, aggressive (Gleason≥7)), controlling for potential confounders. Results: Risk was increased among men in management (overall PCa OR=2.2, 95% CI 1.4 to 3.2; aggressive PCa OR=2.2, 95% CI 1.3 to 3.5) and military occupations (overall PCa OR=3.4, 95% CI 1.7 to 7.0; aggressive PCa OR=3.5, 95% CI 1.5 to 8.3). Risks were also elevated for management and military-specific jobs based on 3-digit level Standard Occupational Classification definitions. Sensitivity analyses accounting for access to medical care did not show significant differences. Conclusions: Our study provides some evidence for increased risk of PCa among men in management and military occupations, which is consistent with the published literature. Additional research is needed to clarify the drivers of the associations between these occupations and PCa.